Emission characteristics of Cd, Pb and Mn from coal combustion: Field study at coal-fired power plants in China - Deng, Shuang; Shi, Yingjie; Liu, Yu; Zhang, Chen; Wang, Xiangfeng; Cao, Qing; Li, Songgeng; Zhang, Fan (Fuel processing technology, 2014)
A full-scale field study of cadmium (Cd), lead (Pb) and manganese (Mn) emissions from coal combustion was carried out at six coal-fired power plants in China. Simultaneous sampling of coal, bottom and fly ashes, flue gas, and the byproducts from wet FGD process was performed. The formation of particulate bound Pb in flue gas was strongly affected by chlorine content in coal, ratio of trace metal content to ash content in coal and loss-on-ignition of fly ash. However, these factors had no significant effect on formation of particulate bound Cd and Mn in flue gas. Release rates and enrichment factors of the metals were calculated for comparison. Mass balances of the trace metals in the tested power plants were carried out. It was found out that Pb has the highest release rate among the trace metals. Most of the trace metals entered into bottom and fly ashes in the combustion process. Pb was enriched more in fly ash relative to Cd and Mn. The existing air pollution control devices at the power plants were able to remove most of the metals in the flue gas. Emission factors of Pb, Cd and Mn were calculated for each tested power plant. •Pb is more enriched in fly ash than in bottom ash.•Cd and Mn are partitioned more equally between fly ash and bottom ash.•Chlorine content in coal, LOI of fly ash and M/A ratio affect particulate Pbformation.•TheAPCDs can remove most of Pb,Cd and Mn in flue gas.